Faktor Determinan Harga Saham Sektor Real Estate dan Properti - Muhammad Nur Alfi; Roy Budiharjo (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
This study aims to determine the effect of return on asset (ROE), debt to equity (DER), and total asset turnover (TATO) on stock returns on property & real estate companies on the Indonesia Stock Exchange from 2014 to 2018. The sample is 37 companies chosen by using a purposive sampling technique. The regression analysis shows the mixed results: ROE has a significant positive effect on stock returns, the DER does not have a significant effect, while the TATO has a significant negative effect on stock returns. This study provides implications and suggestions for future researchers and practitioners to predict stock returns in the property and real estate sectors from the company's fundamental factors.